The analysis and design of linear circuits - Thomas, Roland E. (Wiley, 2006)
Thomas and Rosa offer a learn-by-doing approach to linear circuits. They discuss the major elements of circuit design (including Laplace transforms, new passive and active elements, pole-zero diagrams, Bode diagrams, Fourier series, and time-varying circuits), and provide skill-building exercises. Furthermore, they show how to evaluate and select the best design from several correct approaches. This new edition covers five of today's most widely used programs: Excel, MATLAB, Mathcard, Electronics Workbench, and PSpice.